2019
DOI: 10.1186/s12931-019-1256-y
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of drug-induced hepatotoxicity on anti-tuberculosis therapy: a case control study

Abstract: BackgroundThere are limited data available on whether drug-induced hepatotoxicity (DIH) affects the clinical outcomes of tuberculosis (TB) treatment. We explored the effects of DIH on the clinical course and outcomes of pulmonary TB.MethodsIn this retrospective cohort study, we included patients with culture-proven pulmonary TB treated in a tertiary hospital from 2013 to 2016. DIH was defined as proposed by the official American Thoracic Society statement. We compared the clinical outcomes of DIH and non-DIH p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…In 1994, morphological damage of myocardial mitochondria in septic cardiomyopathy was first described in an animal model ( 26 ). Studies have shown that the ultra-microstructural abnormalities of myocardial mitochondria in septic cardiomyopathy include swelling, ridge loss, matrix clearance, rupture of internal vesicles, and damage to internal and external membranes ( 27 , 28 ), which are closely related to mitochondrial dysfunction ( 29 ). Specifically, ultra-microstructural abnormalities lead to the destruction of the OXPHOS process and further reduce adenosine triphosphate (ATP) production.…”
Section: Mitochondrial Ultrastructural Damage and Decreased Atp Productionmentioning
confidence: 99%
“…In 1994, morphological damage of myocardial mitochondria in septic cardiomyopathy was first described in an animal model ( 26 ). Studies have shown that the ultra-microstructural abnormalities of myocardial mitochondria in septic cardiomyopathy include swelling, ridge loss, matrix clearance, rupture of internal vesicles, and damage to internal and external membranes ( 27 , 28 ), which are closely related to mitochondrial dysfunction ( 29 ). Specifically, ultra-microstructural abnormalities lead to the destruction of the OXPHOS process and further reduce adenosine triphosphate (ATP) production.…”
Section: Mitochondrial Ultrastructural Damage and Decreased Atp Productionmentioning
confidence: 99%
“…Long-term use can cause side effects such as skin reaction, gastrointestinal dysfunction, and neurological dysfunction. 8,9 Hepatotoxicity is a side effect that most type of first-line ANTI-TB DRUG has. This effect also has the most serious impact.…”
Section: Introductionmentioning
confidence: 99%
“…Grade I is marked by an increase of ALT > 1.25 -≤ 3x normal, grade II increase > 3 -≤ 5x normal, grade III ALT increase > 5 -≤ 10x normal, and grade IV if ALT increase > 10x normal. 5,8 Studies conducted in several countries found that the incidence of anti-TB drug-induced hepatotoxicity varies. For example, a study in Nepal showed a prevalence of anti-TB drug-induced hepatotoxicity of 38%, while in Iran, the prevalence of anti-TB druginduced hepatotoxicity reaches 27%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatotoxicity is one of the adverse effects of ATD that could contribute to treatment interruption and may increase the risk of acquired resistance 4 . Some of the first-line ATD, isoniazid (H), rifampicin (R), and pyrazinamide (Z) are metabolized in the liver and have the potential to cause hepatotoxicity 5,6 .…”
Section: Introductionmentioning
confidence: 99%